Downward drifting Sticky Floors? - Evidence on the Development of Wage Inequality Among Foreigners in Germany - Johannes Ludsteck; Florian Lehmer (European Regional Science Association (ERSA), 2013)
We employ the German social security register data to analyze the development of wage inequality among foreigners in Germany. The data show a sharp increase of wage inequality which exceeds the size observed for natives. The decomposition methods proposed by DiNardo et al. (1996) are employed to investigate whether the increase in wage inequality can be explained by the composition of work force characteristics. Our results show that observable characteristics play a significant role in the period 1984–1993. In later years the effect is important for the upper tail of the wage distribution only. This suggests that the valuation of foreign workers' characteristics must have changed rapidly in the last 15 years.
Keywords: J31; J24; J15; 330; Migration; Wage Inequality